Efficacy and safety of transarterial chemoembolization combined with lenvatinib and camrelizumab in patients with BCLC-defined stage C hepatocellular carcinoma - Wu, Juan; Zeng, Jia; Wang, Huiwen; Huo, Zhuoni; Hou, Xunbo; He, Dongfeng (Frontiers in Oncology, 2023)
Objective To investigate the effectiveness and safety of combining transarterial chemoembolization (TACE) with lenvatinib and camrelizumab in patients with Barcelona Clinic Liver Cancer (BCLC) stage C hepatocellular carcinoma (HCC). Methods We retrospectively analyzed 141 patients with BCLC stage C HCC: 57 were treated with TACE combined with lenvatinib plus camrelizumab (T + L + C), 41 were treated with TACE combined with camrelizumab (T + C), and 43 were treated with TACE (TACE). The primary outcomes were overall survival (OS) and progression-free survival (PFS), and the secondary outcomes were the objective response rate (ORR) and adverse events (AEs). Factors that affected survival were identified via Cox regression analysis. Results Comparison of the three groups revealed a significant difference in the median overall survival (mOS), 19.8 months (95% CI 15.7–23.9) in the T + L + C combined group vs 15.7 (95% CI 13.1–18.3) months in the T + C combined group vs 9.4 (95% CI 6.2–12.5) months in the TACE group (P < 0.001). The median progression-free survival (mPFS) was significantly better in the T + L + C combination group than in the T + C combination group and the TACE group [11.4 (95% CI 7.6–15.3) months vs 8.4 (95% CI 6.2–10.5) months vs 4.8 (95% CI 3.2–6.3) months, respectively, P < 0.001)]. The objective response rate (ORR) (57.9%) and the disease control rate (DCR) (75.4%) patients in the combined T + L + C group were higher than those in the other two groups. More patients in the combined T + L + C group experienced AEs, with 16 (28.1%) patients experiencing AEs of grade 3 or higher. Conclusions In patients with BCLC stage C HCC, those receiving the T + L + C combination demonstrated a superior survival benefit and acceptable safety profile compared patients receiving either TACE or the T + C combination.